Analysis and optimization of modulation transitions in medium-voltage high-power converters - Fernandez-Rebolleda, Hector (2022)
Different modulation techniques need to be combined in medium-voltage high-power variable-speed drives as the fundamental output frequency changes. Due to this fact, transitions between different modulation techniques are required in a real-time converter operation. However, these transitions may generate phase overcurrent due to changes in the switching patterns. This article presents a method that analyzes and models the modulation transitions. It also identifies the optimal fundamental period angle interval where the transition should take place to minimize or eliminate any overcurrent. The proposed method is generic and can be extrapolated to any converter topology and modulation technique. It is demonstrated for transitions between selective harmonic elimination pulsewidth modulation and space vector modulation on a three-level neutral-point-clamped converter through simulations and experimentally validated in a 45-kW scaled-down converter and 6.5-MW full-scale drive.